Prevalence of occupational stress among secondary school teachers in Kuala Lumpur, Malaysia - Ismail, Siti Najiha; Abdul Rahman, Haliza; Abu Bakar, Azrin Shah; Zaremohzzabieh, Zeinab (Ministry of Health of Azerbaijan Republic, 2023)
The workload of teachers is a contributing factor to their occupational stress. It may cause depression and anxiety, which may impair the teacher's ability to carry out their daily tasks or perform well at work. Objective: This study aimed to identify the prevalence of occupational stress among secondary school teachers in Kuala Lumpur Malaysia. Methodology: This cross-sectional study with a sample of 161 secondary school teachers was conducted using simple random sampling. The data were collected through a structured questionnaire on sociodemographics, task responsibility, time constraints, and student attitude and analyzed using SPSS version v.26. Results: The prevalence of occupational stress was about 40.4 which was high. We found that secondary school teachers experience a moderate level of occupational stress, with a mean score ranging from 2.34 to 3.67. Prevalence of occupational among secondary teachers was associated with task responsibility, time constraints, and student attitude. Furthermore, with a p-value of less than 0.05, there is a significant difference between the prevalence of occupational stress and task responsibility, time constraints, and student attitude. Conclusion: In conclusion, occupational stress should receive attention to reduce the prevalence of occupational stress among secondary school teachers. This study concludes that occupational stress among Malaysian secondary school teachers in urban areas in Kuala Lumpur was high compared with other studies. Therefore, occupational stress should receive attention on this issue to reduce the prevalence of occupational stress among secondary school teachers.